Volume and heat transport in the South China Sea and maritime continent at present and the end of the 21st century - Samanta, Dhrubajyoti (2021)
Ocean transports through the Southeast Asian Seas connect the western tropical Pacific and Indian Oceans, thereby exerting an important role in regional and global climate. High-resolution regional ocean model simulations over the South China Sea (SCS) and maritime continent are used to study the mean and seasonally varying thermohaline structure and volume transport through the straits surrounding the SCS. Diversity in the vertical structure of these straits is not only indicative of the role of widely varying bathymetry but also strong seasonality associated with monsoonal currents. The presence of a Pacific water mass in intermediate and deep layers of the Luzon Strait points to a key pathway between the Pacific and Indian Oceans. Further, examining a suite of global, high-resolution model simulations reveals the projected changes in the regional upper ocean transports due to anthropogenic radiative forcing by the end of the 21st century. The global models predict an increase in heat and volume transport through the Luzon and Karimata Straits, and a decrease thereof through the Makassar and Lombok Straits by the end of the century. Overall, these changes impute additional net convergence of heat and volume in the SCS, a significant reduction of sea surface salinity and mixed layer depth, and an increase in the upper-ocean heat content of the region. As the SCS serves as a regional heat capacitor and is impacted by the global thermohaline circulation locally via Indonesian Throughflow, these predicted changes have the potential to impact climate over the Indo-Pacific region and globally.